La géopolitique de l'Union Européenne pour les régions ultrapériphériques : - Gutemberg de Vilhena Silva; Jadson Luis Rebelo Porto; Paula Gabriele Sena dos Santos; Miguel Dhenin (Confins)
Located in the north of South America, French Guiana in it’s outermost condition, is part of na important geographical position for the European Union (EU). From the analysis of documents about the outermost regions (OR’s), reports concerning the results of recent european fundings for the regional integration of French Guiana; as well as analysis of the importance of Kourou spaceport for the EU, it is possible to indicate the following guiding question of this article: What are the reticular-territorial joint strategies adopted by the European Union in the specific case of French Guiana? In the first section, we discuss the construcion of priorities and investments for the OR’s in general, however, we estabilished more detailed analysis of French Guiana.. In the second section we analyze two subjects: a) the European strategies and the impacto n the Guiana when using the Korou spaceport; b) some of the results of the first edition of POAmazonia (2007-2013), attempting to assess accurately and updated the regional geopolitics in which French Guiana is inserted through the European guidelines.